Highlighting nuances of blue light phototherapy: Mechanisms and safety considerations. Issue 2 (25th October 2022) - Uzunbajakava, Natallia E.; Tobin, Desmond J.; Botchkareva, Natalia V.; Dierickx, Christine; Bjerring, Peter; Town, Godfrey
Abstract: The efficacy of blue light therapy in dermatology relies on numerous clinical studies. The safety remains a topic of controversy, where potentially deleterious effects were derived from in vitro rather than in vivo experiments. The objectives of this work were (1) to highlight the nuances behind "colors" of blue light, light propagation in tissue and the plurality of modes of action; and (2) to rigorously analyze studies on humans reporting both clinical and histological data from skin biopsies with focus on DNA damage, proliferation, apoptosis, oxidative stress, impact on collagen, elastin, immune cells, and pigmentation. We conclude that blue light therapy is safe for human skin. It induces intriguing skin pigmentation, in part mediated by photoreceptor Opsin‐3, which might have a photoprotective effect against ultraviolet irradiation. Future research needs to unravel photochemical reactions and the most effective and safe parameters of blue light in dermatology. Abstract : Blue light phototherapy provides dermatological and systemic disease treatments. Its therapeutic effect relies on well‐orchestrated chromophores and photoreceptor groups in skin and hair follicle cells. Through a "slightly ajar" curtain, we are evidencing this interplay between photons and cells, eager to unravel its complexity to create safer and more effective therapies. This work synergizes biophotonics, photodermatology and cutaneous biology highlighting the "shades" of blue light; modes of action and the balance between risks and benefits of blue light therapy.